PELAKSANAAN UPACARA ADAT PERKAWINAN MASYARAKAT DAYAK DESA DI DESA PAKAK KECAMATAN KAYAN HILIR KABUPATEN SINTANG - NIM. A1011191162, MARDIANA DESY (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac Dayak Village Dayak are a Dayak tribe who live in the Pakak Village area, Kayan Hilir District, Sintang Regency, West Kalimantan. Until now, people are still guided by customary law in carrying out their daily lives. At the traditional wedding ceremony of the Dayak Village Community in Pakak Village, Kayan Hilir District, Sintang Regency, there was also a shift in terms of tools and equipment. One example of a very visible shift in traditional wedding ceremonies is that as time goes by, many of the tools used in wedding ceremonies are then replaced or eliminated. Even traditional wedding ceremonies can be carried out as simply as the bride and groom can afford. However, nowadays there has been a shift in the tools and equipment used in traditional wedding ceremonies due to various factors.Based on the problem formulation, namely: